2016
DOI: 10.1007/s00216-016-9533-9
|View full text |Cite
|
Sign up to set email alerts
|

Development and application of a comprehensive lipidomic analysis to investigate Tripterygium wilfordii-induced liver injury

Abstract: Lipid metabolic pathways play pivotal roles in liver function, and disturbances of these pathways are associated with various diseases. Thus, comprehensive characterization and measurement of lipid metabolites are essential to deciphering the contributions of lipid network metabolism to diseases or its responses to drug intervention. Here, we report an integrated lipidomic analysis for the comprehensive detection of lipid metabolites. To facilitate the characterization of untargeted lipids through fragmentatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…Lysophosphatidylcholine (LysoPC) is a class of substance from the glycerophospholipids and plays a vital role in various liver disease. In the present study, the level of LysoPC was significantly increased in mice from the triptolide treatment group, which was consistent with another report (Xie et al, ). Previously studies revealed that LysoPC was a strong proinflammatory mediator, which could lead to the release of arachidonic acid by activating phospholipase A2 in two signaling pathways.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Lysophosphatidylcholine (LysoPC) is a class of substance from the glycerophospholipids and plays a vital role in various liver disease. In the present study, the level of LysoPC was significantly increased in mice from the triptolide treatment group, which was consistent with another report (Xie et al, ). Previously studies revealed that LysoPC was a strong proinflammatory mediator, which could lead to the release of arachidonic acid by activating phospholipase A2 in two signaling pathways.…”
Section: Discussionsupporting
confidence: 93%
“…A UPLC‐MS lipidomic analysis revealed that energy lipid modification, membrane remodeling, potential signaling lipid alterations and abnormal inflammation response were associated with Tripterygium wilfordii Hook. F (TWHF)‐induced liver injury (Xie et al, ). Recently, an ultra performance liquid chromatography‐electrospray ionisation‐time of flight mass spectrometry (UPLC‐ESI‐QTOFMS) urine metabolomic survey found that eight potential biomarkers associated with tryptophan, pantothenic acid and porphyrin were related to triptolide toxicity and licorice had potential protective therapeutic effects against such toxicity (Wang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past 20 years, metabolomics has been used in many fields, such as responses to toxicology (Shi et al, ; Xie, Zhou, et al, ), nutrition (Guasch‐Ferre, Bhupathiraju, & Hu, ), disease diagnosis (Bujak et al, ; Li et al, ) and mechanism of drug action (Du et al, ; Wishart, ). Metabolomics is ideally positioned to address the challenges of toxicology in the twenty‐first century, as it provides accurate knowledge of disturbed biochemical pathways related to the extent of the toxic insult and its underlying mechanisms (Ramirez et al, ).…”
Section: Amniotic Fluid Metabolomicsmentioning
confidence: 99%
“…Indeed, the metabolic features of AF related to pathological phenomena may result in the discovery of new biomarkers that may improve clinical management of numerous conditions (Feng et al, ). Metabolomics has been widely applied in research on disease diagnosis (Bujak, Struck‐Lewicka, Markuszewski, & Kaliszan, ), drug action mechanism (Du et al, ; Wishart, ) and toxicity (Shi et al, ; Xie, Zhou, et al, ) during the past decades. Therefore, metabolomics may also be the most suitable strategy for evaluating the safety of CMs during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation